1999
DOI: 10.1007/s004310051262
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transporter type 1 deficiency: a study of two cases with video-EEG

Abstract: Glucose transporter type 1 (GLUT1) deficiency is an inborn error of glucose transport. Clinical manifestations are presumed secondary to reduced glucose transport across the blood brain barrier, and include seizures, abnormal tone, developmental delay and hypoglycorrhachia. A high index of suspicion is important as GLUT1 deficiency is a potentially treatable cause of mental retardation. We studied two affected children by continuous video-EEG in order to better understand the cause of the clinical manifestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 6 publications
0
18
0
1
Order By: Relevance
“…Interestingly, Korenke et al [7] observed that epileptical discharges and slowing of background activity recorded in two patients in the fasting state were fully reversible following food intake. This reflects the clinical observation that seizure activity and motor deficits in some patients clearly increase in the fasting state [6,8]. Based on this observation we suggest an EEG following a 12-18 h fast and a post-prandial EEG.…”
Section: Electroencephalographymentioning
confidence: 63%
See 3 more Smart Citations
“…Interestingly, Korenke et al [7] observed that epileptical discharges and slowing of background activity recorded in two patients in the fasting state were fully reversible following food intake. This reflects the clinical observation that seizure activity and motor deficits in some patients clearly increase in the fasting state [6,8]. Based on this observation we suggest an EEG following a 12-18 h fast and a post-prandial EEG.…”
Section: Electroencephalographymentioning
confidence: 63%
“…To date, 24 patients with GLUT1 deficiency syndrome have been published [6,8,16,17,43,46,70,83] and several additional cases described in abstract form [38,39,40,45,62]. In general, the clinical presentation is heterogeneous and often unspecific.…”
Section: Clinical Presentationmentioning
confidence: 96%
See 2 more Smart Citations
“…In some patients symptoms and EEG abnormalities can be aggravated by fasting and reversed by food intake. 27,[55][56][57] Thus, EEG recordings in preprandial (12-18h fast) and postprandial settings can be of some diagnostic value. Ictal EEG features have been characterized as focal slowing or epileptiform discharges in infants and generalized 2.5-4Hz spike-wave patterns in children.…”
Section: Reviewmentioning
confidence: 99%